PARTISIPASI MASYARAKAT DALAM FORMULASI PERENCANAAN PROGRAM PENINGKATAN POPULASI DAN PERFORMANCE SAPI MADURA MELALUI INSEMINASI BUATAN - Arif Rahman Hakim; Sumartono .; Bambang Santoso Haryono (Universitas Tribhuwana Tunggadewi, 2015)
Beef and buffalo meat self-supporting program rolled out by Ministry of Agriculture which is planned to be reached in 2010 is in fact failed to be achieved, so that the targeted reset in 2014 but not reached either. It is a sad reality considering the potential of nature that we have that is rich in biodiversity. Proper planning is needed to overcome these problems. The role of Government, society and private sector in the planning process is expected to produce plannning that is able to overcome the problems of meat self-supporting program. The research focused on the planning formulation process of madura cow population and performance excalation program including the stages of planning, actor involved in the planning, and the result of the planning, societal participation can be seen in the planning process, the form of participation and level of participation as well as the supporting and inhibiting factors to the societal participation. Societal participation in the planning process, specially on the village/district and subdistrict development planning deliberation forum become a proper means for the society to express their aspiration because on this stage of planning society is still able to deliver their aspiration directly.